Physical And Organoleptic Characteristics Of Tiwul Cookies - Bidari, Ananda Rahma Ayu; Rosida, Dedin F (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
Cookies are a type of biscuit made from soft dough, high in fat, relatively crispy when broken, and have a solid cross-section. This study focuses on developing cookie products using tiwul flour as an alternative carbohydrate source to replace wheat flour. The addition of jewawut of high-starch food ingredients is needed to improve the texture of the cookies. Animal protein food ingredients used in this study include freshwater snail and anchovy flour. This research aims to determine the effect of the proportion of tiwul flour and jewawut flour with the addition of freshwater snail flour and anchovy flour on the physical and organoleptic characteristics of cookies and determine the best treatment based on physicochemical parameters. The research design used in this research was a Complete Randomized Design (CRD) with a 2-factor factorial pattern with 2 replications. The treatment used was proportions of tiwul and jewawut flour (80%:10%, 70%:20%, 60%:30%) and the addition of anchovy and freshwater snail flour (10%, 5%:5%, 10%). The observation variable data was tested statistically using analysis of variance at a=5% using the DMRT follow-up test. The best treatment with the proportion tiwul 60% : jewawut 30% : anchovy 5% : freshwater snail flour 5%. Which was the best treatment with a water content of 3,79%, ash content of 3,25%, fat content of 26,11%, color of 2,47 (brown), aroma of 4,03 (typical of cookies), taste of 3,70 (sweet savory), and texture 3,73 (crunchy)